PARAMETERS OF SEISMOTECTONIC DEFORMATIONS OF THE EARTH'S CRUST IN THE BAIKAL RIFT ZONE BASED ON SEISMOLOGICAL DATA - Mel'nikova V.I.; Radziminovich N.A. (My University, 2007)
The peculiarities of the deformation of the Earth’s crust in the Baikal rift zone (BRZ) are studied sufficiently well in the seismological aspect. At the same time, problems related to the separation of local and regional characteristics of seismotectonic deformations (STD) and to the quantitative estimate of the seismogenic component of the general tectonic process remain pressing. The objective of this work is to distinguish the regimes of seismotectonic deformation of the Earth’s crust in the BRZ during a 50-yr (1950–1999) period of seismological observations and to determine the mean velocities of STD.